The Influence of Distribution of Zakat, Infaq and Sadaqah (ZIS) Funds and Economic Generation on the Social Welfare of the City/Regency Level in East Java in 2021-2023 - Herlin Fauzia Safitri; Fatimatuz Zahroh; Eko Suprayitno (International Journal of Management Research and Economics, 2024)
Economic development is an important strategy in achieving social prosperity, and many development theories emphasize the importance of economic growth as the key to reducing poverty and increasing the level of welfare. One approach that is widely known is the theory of economic growth which places economic growth as the main priority in efforts to overcome the problem of poverty and achieve a higher level of prosperity. This research uses quantitative research with quantitative descriptive analysis and path analysis techniques with the help of the Eviews 12 program. Research results: Distribution of Zakat, Infaq and Alms Funds (ZIS) and economic growth have a partial and simultaneous effect on the welfare of the City/Regency community in East Java 2021-2023.